2014
DOI: 10.1159/000357369
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Cell Delivery: Substrates and Scaffolds for Cell Therapy

Abstract: Retinal degeneration, associated with loss of photoreceptors, is the primary cause of permanent vision impairment, impacting millions of people worldwide. Age-related macular degeneration and retinitis pigmentosa are two common retinal diseases resulting in photoreceptor loss and vision impairment or blindness. Presently, available treatments can only delay the progress of retinal degeneration, and there are no treatments that can restore permanent vision loss. Research is underway to develop methods of regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
(94 reference statements)
0
19
0
Order By: Relevance
“…A number of bioengineering approaches have been used for delivery for cardiac, retinal and corneal cell replacements (Cutts et al, 2015; Kundu et al, 2014; Ozcelik et al, 2014). The use of a natural or synthetic biodegradable matrix, usually as a membrane seeded with stem/progenitor cells, can provide the appropriate milieu for cell growth, and when placed directly on the target or diseased site of an organ (sometimes termed a ‘patch’ or ‘wrap’), resulting in efficient cell engraftment and homogenous cell distribution.…”
Section: What Is the Best Way To Deliver Stem Cells To The Gut?mentioning
confidence: 99%
“…A number of bioengineering approaches have been used for delivery for cardiac, retinal and corneal cell replacements (Cutts et al, 2015; Kundu et al, 2014; Ozcelik et al, 2014). The use of a natural or synthetic biodegradable matrix, usually as a membrane seeded with stem/progenitor cells, can provide the appropriate milieu for cell growth, and when placed directly on the target or diseased site of an organ (sometimes termed a ‘patch’ or ‘wrap’), resulting in efficient cell engraftment and homogenous cell distribution.…”
Section: What Is the Best Way To Deliver Stem Cells To The Gut?mentioning
confidence: 99%
“…Evidence has shown that using a polymer scaffold could offer better manipulation of the extracellular environment and afford the most appropriate degree of cell attachment, differentiation, and maintenance of apposite function (Tomita et al, 2005;Kador and Goldberg, 2012;Kundu et al, 2014). Current ongoing preclinical trials are applying various types of scaffolds for monolayer stem cells transplantation.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…There are various techniques used to manufacture scaffolds for the subretinal space, such as particulate leaching, electrospinning and freeze drying, microfabrication, and solvent casting, the last 2 being the most used. 91 Regardless of their nature, scaffold size should range from 5 to 90 mm due to the limited subretinal compartment and be biocompatible, mechanically robust, flexible to be easily implantable, and porous to support formation of the polarized layer. Ideal scaffolds should (i) enable formation of a polarized RPE monolayer performing designated functions, (ii) have sufficient strength and flexibility to be transplanted at the back of the eye, (iii) support integration of RPE to Bruch's membrane, and lastly (iv) should be inert to the eye.…”
Section: Scaffold Material Fabrication Technique and Propertiesmentioning
confidence: 99%